MODEL PREDIKSI KESULITAN KEUANGAN DENGAN RASIO KEUANGAN (Studi kasus Pada Perusahaan Manufaktur di Indonesia yang telah terdaftar selama 5 Tahun di BEI 2008-2012) - Diaz Lunardi Santoso (Universitas Mercu Buana, 2017)
This research aimed to figure financial distress model and to determined wihich financial ratios can predict financial distress for 1 year; 2 years; and 3 years before. This research was using samples of manufacturing industry thst listed on The Indonesian Stock Exchange in 2008-2012. Based on purposive sampling method, the research samples total are 160 manufactured companies. To figure the model, this research used logistic regression. This research indicated that financial ratios likes leverage, profitability, activity, RE to Total Assets, Market value of Equity to Book Value of Debt can predict financial distress 1 year; 2 years; and 3 years before. These financial ratios can predict above 64% of financial distress for 1 year; 2 years, and 3 years before, while around 36% were influeced by others factors. The predicting model for 1 year have 96,3% clasification accuracy ,while 2 years model have 96,3% clasification accuracy and 3 years model have 92,5% clasification accuracy